THE EFFECT OF OBESITY ON IMMUNITY, CALCIUM, AND TOTAL CHOLESTEROL IN FEMALE (World Bulletin of Public Health, 2022)
Obesity is an excessive or an increased accumulation of fat that affects health. It was caused if an energy imbalance between the calories that enter and their burns in the body. 36 participants were included in this study. The subjects who are eligible for the study were adults of female, age 23-75 years, categorized according to Body Mass Index (BMI) into 3 groups. Our results revealed that the percentage of female were 35.48% of women normal weight group (18.5-24.9 Kg/m2), 35.48% in the increase in weight group (25-29.9 Kg/m2), and 29.04% in the first category fat group (30-34.9 Kg/m2 ). The current study showed that the level of white blood cells (WBC) and neutrophils were higher in the first category of the fat group compare to other two groups, total cholesterol were higher in first category of fat group compared to other groups. The levels of calcium were higher in normal weight of women compare to other groups. Finally, a weak positive correlation was estimated between BMI and total cholesterol level, negative correlation was estimated between BMI and serum calcium level
Keywords: Obesity; immunity; calcium; total